Influence of Authentic Leadership on Employees’ Taking Charge Behavior: The Roles of Subordinates’ Moqi and Perspective Taking - Wen, Qiuxiang; Liu, Ruhong; Long, Jing (Frontiers in Psychology, 2021)
How to motivate employees to break through the role constraints and show more initiative determines the success or failure of a company’s future development. Taking charge behavior refers to the behavior that individuals influence the change of organizational function through voluntary and constructive efforts, which is a challenging organizational citizenship behavior. This study investigates the underlying mechanism and boundary condition of authentic leadership (AL) on employees’ taking charge behavior based on role identity theory and the literature concerning perspective taking. Matched data were collected from a multi-source sample that included 146 direct supervisors and 328 subordinates in mainland, China. The empirical results indicate that AL has a positive influence on employees’ taking charge behavior, and subordinates’ moqi mediates the relationship between them. In addition, employees’ perspective taking positively moderated the positive relationship between AL and subordinates’ moqi as well as the mediating effect of subordinates’ moqi in the relationship between AL and employees’ taking charge behavior. Compared with low levels of perspective taking, high levels of that made the influence of AL on subordinates’ moqi stronger, so is the whole indirect effect. This study is the first to explore the influencing mechanism of AL on employees’ taking charge behavior from the perspective role identity theory, thereby enriching the relevant studies and providing practical insights for organizational leaders regarding how to foster employees to take charge.